2004
DOI: 10.1098/rsbl.2003.0103
|View full text |Cite
|
Sign up to set email alerts
|

Immunocompetence and its costs during development: an experimental study in blue tit nestlings

Abstract: The allocation into T-cell-mediated immunocompetence was experimentally increased in 68 out of 139 nestlings by supplementary feeding methionine to half of the nestlings in 15 blue tit nests. Methioninesupplemented nestlings had an increased T-cellmediated immunocompetence, but a reduced growth compared with control siblings. Nestlings that had low initial weights and nestlings that were supplemented with methionine had an increased mortality risk. The investment that nestling blue tits make in immunocompetenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
138
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(145 citation statements)
references
References 21 publications
7
138
0
Order By: Relevance
“…This provides further support for a trade-off between immunocompetence and growth (Soler et al, 2003;Brommer, 2004). In response to exposure to antigens, macrophages release inflammatory cytokines and provoke an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides further support for a trade-off between immunocompetence and growth (Soler et al, 2003;Brommer, 2004). In response to exposure to antigens, macrophages release inflammatory cytokines and provoke an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, maternal antibodies may provide offspring with the benefits of immune defense without the growth suppressive costs of generating an endogenous immune response. Several previous studies have documented suppressive effects of natural infection or experimental immunization on the growth of young animals (Klasing et al, 1987;Fair et al, 1999;Soler et al, 2003;Brommer, 2004). Because differentiation of the specific immune response is largely determined by exposure to antigens, it is poorly developed in neonatal vertebrates with little previous antigenic exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have demonstrated in birds that an immune challenge during development was responsible for a reduction in the growth rate [25,26], which is known to influence the fitness of nestlings [27]. However, those studies have mostly focused on innate immune mechanisms, and the potential role of the transfer of maternal antibodies as a mechanism favouring chick growth in the face of parasitic challenge has often been neglected (but see [28]).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the potential costs associated with the production and maintenance of immune response (Moller et al 1998; but see Klasing 1998), we also examined the relationship between immune response and condition or size. We did not, however, predict the direction of the relationship, because some studies suggest a positive correlation between condition and immune response (Moller et al 1998;Blanco et al 2001), whereas others suggest a trade-off between growth and immune response (Brommer 2004 Clark et al 2006). Crows in this population are socially monogamous, and family groups usually contain auxiliaries of either sex, most of which help to provision the incubating females, nestlings and fledgelings.…”
Section: Introductionmentioning
confidence: 99%